Active drag estimates based on full and semi-tethered swimming tests - Cortesi, M.; Gatta, G.; Zamparo, P. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
During full tethered swimming no hydrodynamic resistance is generated (FD = 0 since v = 0) and all the swimmer`s propulsive force is utilized to exert force on the tether (FT). During semitethered swimming, propulsive force can be made useful to one of two ends: exerting force on the tether (FST) or (actively) overcoming drag in the water (FD = Da). The quantity FT -FST (the "residual thrust") should, thus, correspond to Da. In this study we explored the possibility to estimate Da based on full tethered and semi-tethered swimming tests (residual thrust method: DaST = FT - FST). We then compared these values with passive drag values (Dp) and values of active drag calculated by means of the "planimetric method" (as DaPL = Dp .1.5). Speedspecific drag (k = D/v2) in passive conditions (kp) was about 26 N m2 s2 and in active conditions (ka) was about 37-38 N m2 s2 (with either method); thus, DaST > Dp and DaST = DaPL. We can thus conclude: i) that since these two approaches (planimetric method and residual thrust method) lead to similar results, they probably measure the same quantity and ii) that active drag is larger (about 1.5 times larger: 38/26=1.46) than passive drag.